THE INFLUENCE OF PRICE, QUALITY, AND RISK PERCEPTION ON BUYING INTEREST IN ALFAMART PRIVATE LABEL PRODUCTS IN BANDAR LAMPUNG - Pupung Dzulhijatussarah; Defrizal Defrizal (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
In the current 4.0 era, retailers are starting to be required to provide various product needs that are of high quality, appropriate prices, and have more value. One of them is Alfamart which innovates to package products with its own brand (private label products). This study used quantitative methods, involving 100 respondents as a sample. During this process, the instruments in the study were tested for validity and reliability. Followed by the classic assumption test consisting of a normality test and a multicollinearity test. Furthermore, conducting a hypothesis test includes multiple linear regression analysis, coefficient of determination (R2), t test and f test. The results of this study are PH variables (price perception) have a negative and insignificant effect on buying interest in private label products, while PK (quality perception) and PR (risk perception) have a positive and significant effect on buying interest in private label products. Then price perception, quality perception and risk perception together simultaneously affect the buying interest of private label products. Therefore, Alfamart should continue to maintain competitive prices to ensure that the prices set reflect the value of the products the company offers. And the products meet the quality standards desired by consumers. If consumers are satisfied with the products sold, trust in the product will increase, and will reduce the impact of consumer concerns on the products that have been purchased.